Cardiomyopathy and cell therapy: ejection fraction improvement and cardiac muscle mass increasing, after a year of bone marrow stem cells transplantation, by magnetic resonance image - Greco, Oswaldo Tadeu; Zotarelli Filho, Idiberto José; Bellini, Marilanda Ferreira; Bilaqui, Aldemir; Souza Júnior, Artur Soares [UNESP]; Ruiz, Milton Artur; Abreu, Ana Carolina de; Jacob, José Luiz Balthazar; Santos, Adriana Barbosa [UNESP] (OMICS International, 2013)
The idiopathic dilated cardiomyopathy (IDC) is one of the major public health problems in the western world. Patients with IDC in functional class IV (New York Health Association - NYHA), even after therapeutic optimization, have high mortality. Stem cell therapy has emerged as a potential therapeutic option for cell death-related heart diseases and several positive effects were assigned to cell therapy in cardiomyopathy. The aim of this study was identify short-term result of cell transplantation in idiopathic dilated cardiomyopathy patients (IDC) who were treated by transplantation of autologous bone marrow mononuclear cells (BMMC). Intracoronary injections of autologous BMMC were performed in eight patients with severe ventricle dysfunction (mean of left ventricle ejection fraction – LEVF=20.03%), cardiac mass muscle around 156.2 g and NYHA between III and IV grades, other 8 IDC patients received placebo. The IDCs were followed - up for one and two years, by magnetic resonance imaging (MRI). The results after one year showed significant improvement in LVEF (mean=181.4) and muscle mass increasing (mean=181.4 g), after two years the LVEF continued improving, reaching a mean of 32.69% and the cardiac muscle mass kept stable (mean=179.4 g). Excepted for one patient, all the other had improvement in the NYHA functional class. The placebo group did not show any improvement. We believe that BMMC implant may be a beneficial therapeutic option for IDC patients.
Keywords: Cardiomyopathy; Bone marrow mononuclear cells transplantation; Left ventricle ejection fraction; Cardiac muscle mass; Magnetic resonance image